Предмет: Алгебра,
автор: leisanstars
Выполни умножение: (u — 5) (9u + 1) (Зи – 9).
Ответы
Автор ответа:
3
(u — 5) (9u + 1) (Зu – 9) = (u*9u +u*1 - 5*9u - 5*1)(3u - 9) = (9u² +u - 45u -5)(3u - 9) = (9u²-44u - 5)( 3u -9) = 9u² * 3u - 44 u *3u - 5 * 3u -9* 9u² +9 * 44u + 5*9 = 27u³ - 132u² - 15u - 81u² + 396u + 45 = 27u³ - 213u² +381u +45
Похожие вопросы
Предмет: Алгебра,
автор: Nastena0307
Предмет: Литература,
автор: turdievaliya
Предмет: Русский язык,
автор: netrinchervotk
Предмет: Психология,
автор: OMGKristallikOMG